Short-term effects of intravitreal Conbercept injection combined with laser photocoagulation on macular edema secondary to ischemic retinal vein occlusion - Liu, Zheng-Feng (Int J Ophthalmol, 2021)
AIM: To observe changes in the best-corrected visual acuity (BCVA), central macular thickness (CMT), and central choroidal thickness (CCT) of patients with macular edema (ME) secondary to ischemic retinal vein occlusion (iRVO) following intravitreal Conbercept injection. METHODS: This retrospective study included 33 eyes from 33 patients who received intravitreal injections of Conbercept for ME secondary to iRVO. Treatments were performed on a 3+pro re nata (3+PRN) basis. All of the patients were examined by fundus fluorescein angiography and spectral domain optical coherence tomography at the first visit. Laser photocoagulation was performed in the nonperfusion area of the retina of all eyes after the first injection. BCVA, CMT, and CCT were observed before and after 6mo of treatment. The number of injections necessary to achieve improved vision was also noted. RESULTS: Following Conbercept treatment, the mean BCVA significantly improved from 0.81±0.39 at baseline to 0.41±0.25 and 0.43±0.29 logMAR in the third and sixth months, respectively (both P=0.000). The CMT of the patients at baseline was 556.75±98.57 µm; 304.78±68.53 and 306.85±76.77 µm 3 and 6mo after treatment, respectively (both P=0.000 vs baseline). The CCTs of the patients at baseline, 3 and 6mo after treatment were 304.63±57.83, 271.31±45.53, and 272.29±39.93 µm, respectively (P=0.026 and 0.035 vs baseline). No severe adverse event relevant to the therapy was noted, and the average number of injections delivered was 3.35. CONCLUSION: Intravitreal Conbercept injection combined with laser photocoagulation appears to be a safe and effective treatment for ME secondary to iRVO in the short-term.